Analysis of power consumption and gas holdup distribution for an aerated reactor equipped with a coaxial mixer: Novel correlations for the gas flow number and gassed power. (12th September 2016) - Hashemi, Nasim; Ein-Mozaffari, Farhad; Upreti, Simant R.; Hwang, Dae Kun
Abstract: The main objectives of this work were to study the gassed power consumption and the local gas holdup for an aerated coaxial mixer composed of a wall scraping anchor and a central impeller. The working fluids were viscous corn syrup solutions at different concentrations. The central impellers were downward pumping pitched blade turbine, upward pumping pitched blade turbine, and hydrofoil A310 impellers. A novel correlation was developed to estimate the gassed power drawn by the coaxial mixer as a function of the gas flow rate, central impeller type, rotational speeds of the anchor and central impeller, and the ungassed power consumption by the anchor and the central impeller. To obtain a master power curve, two new correlations were proposed for the generalized power number and gas flow number of the aerated reactor furnished with the coaxial mixer by incorporating the equivalent rotational speed for the coaxial mixer, speed ratio (central impeller speed/anchor speed), and the central impeller power fraction into these two correlations. The experimental data revealed that by increasing the gas flow rate, the aerated anchor power was increased whereas the gassed power uptake of the central impeller was decreased. It was found that at the higher fluid viscosity and beyond the critical speed ratio equal to 10, the anchor power was increased by increasing the speed ratio (i.e. reducing the anchor speed). To measure the distribution of the gas holdup throughout the aerated reactor, four electrical resistance tomography planes were installed around the reactor. The tomography data showed that the local gas holdup near the vessel wall was not improved by increasing the anchor speed. Graphical abstract: Highlights: The gassed power consumption and the local gas holdup for an aerated coaxial mixer were studied. The sparged gas affected the power consumption of the central impeller and the anchor in different ways. New generalized power number and gas flow number were developed for the aerated coaxial mixer. A new correlation was proposed to predict the gassed power uptake of the aerated coaxial mixer. ERT was used to study the effects of different parameters on the radial gas holdup distribution.